Attitude and opinion of nigerian community pharmacists to self medication practices (2012)
This study evaluated the attitude and opinion of Nigerian community pharmacists on self medication practices with respect to the definition, advantages and disadvantages of self medication, ailments for which self medication should be allowed, as well as measures that may be instituted to ensure appropriate self medication practices. Pretested structured questionnaires were administered to licensed community pharmacists practicing in Southwestern Nigeria between December, 2009 and July, 2010. Descriptive statistics were used to summarize the data. Mann Whitney U and Kruskal Wallis tests were used to evaluate the respondents’ opinions in ordinal variables with p < 0.05 considered statistically significant. Respondents with postgraduate qualification (p < 0.05) believed that self medication solely done by patients without guidance of a health care professional may lead to mismanagement or subtherapeutic management of diseases (66; 91.66%), medication errors and likelihood of disease complications (68; 93.15%). Years of practice had a significant effect on community pharmacists’ perception of advantages of self medication (p < 0.05). Rigorous monitoring of drug advertisement in the media might help in controlling the practice of self medication (63, 86.30%). Respondents believed that keeping the identity of the medications (29; 39.73%) and diagnosis details (19; 27.14%) unknown to patients is unethical. Self medication may be acceptable for fever (53; 74.65%), diarrhea (46; 67.65%) and cough (39; 53.62%), but with specific time limits, for patients on chronic medication who have stable clinical conditions, including asthma (46; 66.67%), hypertension (36; 51.43%) and diabetes (37; 52.86%). Community pharmacists in Southwestern Nigeria possess a good understanding of the concept of self medication, believed the practice should not be discouraged in totality, but should be practiced under controlled conditions, and that public enlightenment may help to ensure safe self medication practices.